Studi Kualitatif Gambaran Kesejahteraan Psikologis Anggota Organisasi Mahasiswa pada Masa Pandemi Covid-19 - Dara Putri Ghassani; Sirril Wafa; Herison Pandapotan Purba (Airlangga University Press, Universitas Airlangga, 2022)
The Covid-19 pandemic has some repercussions for the psychological well-being of students, such as anxiety, stress, and depression. However, few studies have been conducted about this among members of university student organizations. As activities of student organization had been halted during the pandemic, the well-being of the members could be affected. This study aimed to provide an overview of the psychological well-being of members of a university student organization “X” in Yogyakarta during the Covid-19 pandemic. Using an instrumental case study design with theory-driven thematic analysis, three participants were recruited through a purposive sampling. The results revealed that partcipants had positive pictures of some aspects on their psychological well-being and saw other aspects in a more negative light. Specifically, positive appraisals were reported in terms of four aspects: self-acceptance, positive relation with others, authonomy, and self-development. Meanwhile, two other aspects were reported as suboptimal: lack of purpose in life and environmental mastery. This might be due to a lack in goal-setting skills which in turn affect participants’ time management and priority setting between organizational activities, academic pursuit, and personal life.